2013
DOI: 10.1155/2013/190917
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Central Fracture Dislocation after Generalized Seizure during Lumbar Myelography with Iohexol

Abstract: Fracture is a less common complication in seizure patients, and fractures as a consequence of convulsive seizures without direct trauma occur in 0.3% of cases. Acetabular fractures after convulsions are even more rare, and only a few cases of acetabular fracture dislocations, purely caused by convulsive activity, have been reported. Therefore, we report a case of unilateral acetabular central fracture dislocation after a seizure episode, with relevant literature review. The seizure attack occurred after contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…Central acetabular fracture dislocation is seen following high velocity road traffic accidents and rarely following episode of seizures. 11 , 12 , 13 , 14 , 15 , 16 , 17 Rath et al 16 in 1997 suggested that the mechanism of injury around the hip joint following seizures is due to severe uncontrolled muscle contraction of proximal thigh muscle leading to strong force towards the hip joint. Other factor includes severe osteoporosis due to old age and anti-eplietic medications can lead to acteabular fracture and central dislocation of the hip joint following seizures episodes without direct traumatic event.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Central acetabular fracture dislocation is seen following high velocity road traffic accidents and rarely following episode of seizures. 11 , 12 , 13 , 14 , 15 , 16 , 17 Rath et al 16 in 1997 suggested that the mechanism of injury around the hip joint following seizures is due to severe uncontrolled muscle contraction of proximal thigh muscle leading to strong force towards the hip joint. Other factor includes severe osteoporosis due to old age and anti-eplietic medications can lead to acteabular fracture and central dislocation of the hip joint following seizures episodes without direct traumatic event.…”
Section: Discussionmentioning
confidence: 99%
“…Other factor includes severe osteoporosis due to old age and anti-eplietic medications can lead to acteabular fracture and central dislocation of the hip joint following seizures episodes without direct traumatic event. 1 , 2 , 11 , 12 , 13 , 14 , 15 , 16 , 17…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations